Mapping the self-association domains of ataxin-1: Identification of novel non overlapping motifs - Menon, Rajesh; Soong, Daniel; de Chiara, Cesira; Holt, Mark; McCormick, John; Anilkumar, N.; Pastore, Annalisa (PeerJ PrePrints, 2014)
The neurodegenerative spinocerebellar ataxia type 1 (SCA1) is caused by aggregation and misfolding of the ataxin-1 protein. While the pathology correlates with mutations that lead to expansion of a polyglutamine tract in the protein, other regions contribute to the aggregation process as also non-expanded ataxin-1 is intrinsically aggregation-prone and forms nuclear foci in cell. Here, we have used a combined approach based on FRET analysis, confocal microscopy and in vitro techniques to map aggregation-prone regions other than polyglutamine and to establish the importance of dimerization in self-association/foci formation. Identification of aggregation-prone regions other than polyglutamine could greatly help the development of SCA1 treatment more specific than that based on targeting the low complexity polyglutamine region.
Keywords: polyglutamine diseases; confocal microscopy; spinocerebellar ataxia type; FRET; foci; misfolding diseases